The Link between Human Resource Management Practice and Innovative Work Behavior - Shuhaizi, Muhammad Azril; Abdullah, Nor Hazana (Research in Management of Technology and Business, 2021)
Innovative work behavior is considered one of the key variables in solving new competitive edge problems. It is a multi-dimensional variable that include creating, encouraging and introducing innovative ideas. In order to enhance the innovative work behavior among employees, organizations need to implement human resource practices that could encourage this behavior. Therefore, the purpose of this research is to study the link between human resource practices (HRP) with innovative work behavior among F&B medium sized enterprises employees in Malaysia. This research was a quantitative study where questionnaires were used to collect the data. A total of 400 questionnaires were collected from the employees among F&B medium sized enterprise which in Penang, Perak, Selangor, Kuala Lumpur, and Johor using convenience sampling. Data were analyzed using descriptive analysis and Spearman’s correlation analysis. It was found that there are significant relationships between human resource management practices and innovative work behavior. The finding of this study highlights the importance of HRPs in promoting innovative work behavior.